The Late Lithuanian Greimas: Intentions and Reception - Mačianskaitė, Loreta (Semiotika, 2022)
The main research material consists of Algirdas Julius Greimas’s texts written during the transition period, when Lithuania was parting with Soviet rule (1989–1991), mainly his “Baltos lankos” column in Literatūra ir menas weekly periodical as well as various texts by other authors on Greimas’s texts along with memoirs, letters and obituaries. The study has two aims: 1) to find a conceptual approach for analyzing Lithuanian texts by the late Greimas, 2) to identify points of change in the semiosphere of Lithuanian culture. Greimas’s own semiotic method, namely, a structure of four Senders is used to describe his texts. The theoretical context of Juri Lotman’s cultural semiotics is a more permanent intellectual context for this study, and some of the terms are useful in more than one aspect. The readers’ attitudes towards Greimas’s texts highlight how the core and periphery change in the semiosphere: the period of cultural activity and openness and the internal cultural barriers appearing at the same time, the gradual passivation of culture and cases of sporadic creative relationships.
Keywords: Greimas; Lotman; four types of Senders; semiosphere; Post-Soviet Lithuania